Kajian Alokasi Kebutuhan Ruang di Provinsi Sumatera Utara - Dessy Eresina Pinem; Bambang Benediktus Sianipar; Purnama Purnama (Department of Urban and Regional Planning, Diponegoro University, 2015)
Following development pressures, many natural land uses have increasingly changed to built-up areas for various functions such as housing, offices, shops, roads and parking space. This condition implies on the decrease of space availability for agriculture, vegetable planting, and horticulture. In fact, the agriculture products are required for the local food security. In the case of North Sumatera, the development of leading sectors in palm and rubber industries requires more spaces, creating spatial rivalry against other sectors. The research aimed to analyze the spatial development needs in North Sumatera Province in accordance with the land availability and suitability. In this study, the spatial needs were calculated by considering actual and targeted food consumption levels in 2025, the amount of land required for total population settlement in 2015, for palm plantation, and for agriculture and horticulture farming in 2025. The forecasting of agriculture production was conducted by using simple linear regression. The land suitability and capability were measured through Satuan Kemampuan Lahan (Land Ability Unit) to show the land suitability to protected areas, residential areas, forests, mangroves, cattle grazing, annual agriculture, perennial plants, and others. The results showed that there was a shortage of agriculture land in 2025 about 596,485.44 hectares due to land conversion from agriculture to settlement, plantation, and others. Based on the land suitability of seasonal wet and dry lands, there were 1,410,363.07 hectares of land appropriate for vegetable plantation in 2025 and shortage of land availability for housing about 185,638.54 hectares. The other finding was of the fulfilment of targeted rice production in 2025 as long as the allocated land for agriculture farming remains secured even though its productivity unchanged.